1995
DOI: 10.1111/j.1939-165x.1995.tb00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Time and Freezing Temperature on Clinical Chemical Parameters From Canine Serum and Heparinized Plasma

Abstract: To assess changes in 24 blood constituents in frozen serum and heparinized plasma, blood samples were drawn from 10 clinically normal German Shepherd army dogs. The storage characteristics of nine enzymes (ALP, ALT, amylase, AST, CK, GGT, GLDH, LDH, lipase), and 15 metabolites and minerals (albumin, bile acids, bilirubin, calcium, cholesterol, creatinine, fructosamine, glucose, magnesium, phosphate, potassium, protein, sodium, triglycerides, urea) were studied. Parallel samples of serum and heparinized plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
68
3
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 19 publications
10
68
3
4
Order By: Relevance
“…However, we stored the samples frozen for 8-12 months. This can influence the enzyme values that can decrease during storage (Hunter & Madin, 1978;Thoresen et al, 1995;Tryland & Brun, 2001;Tryland et al, 2002) which could partly explain the lower values observed in this study.…”
Section: Discussionmentioning
confidence: 40%
“…However, we stored the samples frozen for 8-12 months. This can influence the enzyme values that can decrease during storage (Hunter & Madin, 1978;Thoresen et al, 1995;Tryland & Brun, 2001;Tryland et al, 2002) which could partly explain the lower values observed in this study.…”
Section: Discussionmentioning
confidence: 40%
“…Samples frozen for a shorter period of time appeared to have less difference than those samples frozen for longer periods. These results show that freezing can detrimentally affect TP concentrations, especially during longer freezing periods, as other studies have shown in different species [22] or with other blood analytes [23].…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, other parameters, showed clear differences in the type (ALT, AST) or magnitude (ALKP) of age-related change between the species, demonstrating the importance of determining normal values for different age groups of each species. Although biochemical parameters assayed from stored samples should be interpreted with care (Thoresen et al, 1995), our results provide values for both clinically normal adult and juvenile kori and houbara bustards which may prove useful for the interpretation of some laboratory findings in clinical cases.…”
Section: Discussionmentioning
confidence: 99%